Peta Permasalahan Pendidikan Abad 21 di Indonesia - Andika Isma; Adi Isma; Aswan Isma; Ardian Isma (Jurnal Pendidikan Terapan, 2023)
Education is the main foundation for the development and progress of a nation. Through education, people can improve their intellectual capacity, skills and knowledge to face the challenges of an ever-evolving era. However, at present, education is faced with a variety of complex problems that require serious attention. This paper aims to provide a comprehensive overview of the 21st century education problem map, from various aspects that affect it. The research method used is literature review by reviewing several articles and books relevant to the topic. The results showed that there are four major problems in 21st century education, namely: educational infrastructure problems, challenges in curriculum quality and relevance, teaching staff problems, and challenges in distance learning. By overcoming these problems through innovation and collaboration, education in the 21st century can be an effective means to form a generation that is competent, creative, and ready to face future challenges.